(untitled) - Ratti, Oscar (Tokyo, 1973)
Secrets of the Samurai is definitive study of the martial arts of feudal Japan, illustrating in detail the weapons, techniques, strategies, and principles of combat that made the Japanese warrior a terrible foe. It is the only book of its kind in a Western language.
Keywords: Military art and science,Samurai